Convergence - Barro, Robert J. (Journal of Political Economy, 1992)
A key economic issue is whether poor countries or regions tend to grow faster than rich ones: are there automatic forces that lead to convergence over time in the levels of per capita income and product? We use the neoclassical growth model as a framework to study convergence across the 48 contiguous U.S. states. We exploit data on personal income since 1840 and on gross state product since 1963. The U.S. states provide clear evidence of convergence, but the findings can be reconciled quantitatively with the neoclassical model only if diminishing returns to capital set in very slowly. The results for per capita gross domestic product from a broad sample of countries are similar if we hold constant a set of variables that proxy for differences in steady-state characteristics.